The Whisper of Satan in the Story of Adam: An Intertextual Analysis of the Qur’an and the Bible through Julia Kristeva’s Framework - Masbur, Masbur (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
This article investigates the narrative of Satan’s whisper in the story of Prophet Adam by comparing its presentation in the Qur’an and the Bible. Both scriptures depict the moment of temptation as a pivotal rupture in the human-divine relationship, yet they differ significantly in narrative structure, character roles, and theological emphasis. Drawing on Julia Kristeva’s theory of intertextuality, this study explores how the Qur’anic version engages with and transforms the Biblical account through three intertextual mechanisms: excerpt, conversion, and haplology. Employing a qualitative-descriptive approach and library-based research, the analysis focuses on two key passages—Genesis 3:4–7 and Qur’an 20:120–121—to trace how symbolic elements are echoed, revised, or omitted. The findings reveal that the Qur’anic narrative repositions the temptation not as rebellion but as human vulnerability, leading not to inherited sin but to divine forgiveness and guidance. This intertextual reading affirms the Qur’an’s discursive autonomy within a shared Abrahamic symbolic field and demonstrates how intertextual theory can deepen comparative studies of sacred texts.